Process and potential factors to develop problem solving competency in learning electrolysis - Muhamad, Suraiya (Penerbit UTM Press, 2017)
This paper discusses a preliminary study which was undertaken to develop a model of authentic chemistry problem solving competency (PSC) in learning chemistry. Recent poor performance of Malaysian students in the Programme for International Students Assessment (PISA) on problem solving test could be due to a pervasive pattern of low application of higher order thinking skills (HOTS) in solving the open-ended problems in Malaysian teaching and learning scenarios. Hence, this study investigated how secondary school students solve open-ended problems in learning electrolysis and what are the underlying factors of their problem-solving competency. At the beginning, 112 chemistry students from a secondary school in Sarawak were selected as the participants. Semi-structured interviews and think aloud protocol (TAP) were conducted to five selected participants in order to investigate their problem solving processes practice. Quite similar findings have emerged: participants that scored with good score in chemistry problem solving ability test (CPSAT) have higher scientific knowledge and problem solving skills compared to low achieving participants. Scientific knowledge competency and problem solving skills have been identified as the major independent variables to develop chemistry problem solving competency. Outcomes from this study shall be used to design a module for one selected topic in chemistry and to develop a ‘Model of Authentic Chemistry Problem-solving Competency’ for school students in general.